Does Tourism Foster Economic Growth in BRICS Region? Empirical Evidence over 1995-2019 - MISHRA, P. K.; SAHOO, Debasis; ROUT, Himanshu B.; CHAINI, S. R.; KUMAR, Pradip (Journal of Environmental Management and Tourism, 2022)
In the BRICS region, international tourism is considered a significant contributor to employment, forex earnings, and gross domestic product. In this context, this study examined the impact of tourism on the growth of BRICS economies by employing PMG based ARDL panel data analysis technique over an augmented neo-classical growth model during a period from 1995 to 2019. The results support a positive impact of international tourism on the growth of BRICS nations when their levels of human development are controlled in the long run. So, this study adds another feather to the extant empirical evidence of the tourism-led growth hypothesis in the BRICS region. Therefore, the policies of tourism sector development/expansion can supplement in achieving an elevated real economic growth in BRICS economies.